PENGEMBANGAN DAERAH PESISIR DENGAN PEMBERDAYAAN MASYARAKAT NELAYAN DI KAWASAN PESISIR KABUPATEN BADUNG - Prayogi, Putu Agus; Paramita Sari, Ni Luh Komang Julyanti (Jurnal Manajemen Pelayanan Hotel, 2019)
Development of coastal tourism by empowering fishing communities in Badung is one form of development that aims to make fishing communities as local genius of coastal areas. It can directly give benefit to the development of tourism in this area. The model of empowerment of fishing communities which is developed in coastal tourism uses several strategies, namely traditional, direct action, and transformation. The development of coastal tourism with the empowerment of fishing communities is expected to have a positive impact on the economy and socio-culture of fishing communities. Economic impacts can be seen from the direct opinions received by fishing communities from their direct involvement in the development of tourism villages. Whereas the socio-cultural impacts that are felt by the fishing community derives from direct interaction with tourists, such as the fishing community knowing the habits of tourists, using technology and the ability to communicate using foreign languages.Key words : tourism villages, empowerment, economy and socio-culture